2011
DOI: 10.1080/13571516.2011.542955
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Clinical Quality Effects of the Acquisition of Highland Park Hospital by Evanston Northwestern Healthcare

Abstract: In 2004, the Federal Trade Commission brought a legal action retrospectively challenging the 2000 acquisition of Highland Park Hospital by Evanston Northwestern Healthcare in Evanston, Illinois. A major issue in that case was whether the merger had resulted in improved clinical quality at Highland Park. In this paper, we describe the conceptual framework that guided our analysis of that issue and we report our findings. Specifically, we examine numerous quantitative measures of clinical quality. We find little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Using DID methods, Ho and Hamilton (2000) (measuring mortality for heart attacks, strokes, and newborns) and Capps (2005) (using AHRQ quality measures) find little to no effect of hospital mergers on quality. In a case study, the Federal Trade Commission found that the Evanston/Northwestern merger (which it litigated retrospectively) had no impact on quality (Romano and Balan, 2011). Finally, Gaynor et al (2011b) examine the impact of mergers in the United Kingdom.…”
Section: Competition and Antitrustmentioning
confidence: 97%
“…Using DID methods, Ho and Hamilton (2000) (measuring mortality for heart attacks, strokes, and newborns) and Capps (2005) (using AHRQ quality measures) find little to no effect of hospital mergers on quality. In a case study, the Federal Trade Commission found that the Evanston/Northwestern merger (which it litigated retrospectively) had no impact on quality (Romano and Balan, 2011). Finally, Gaynor et al (2011b) examine the impact of mergers in the United Kingdom.…”
Section: Competition and Antitrustmentioning
confidence: 97%
“…For this reason, well-supported claims regarding clinical quality tend to be given more weight than other claims of pro-competitive merger effects. Our methods of evaluating such claims are discussed in detail in Romano and Balan (2011), and so are omitted here in the interest of brevity.…”
Section: Hospital Merger Analysismentioning
confidence: 99%
“…Third, finding results in every direction isn't terribly surprising with such a large number of different outcome measures. Romano and Balan (2011) is an interesting recent study. Romano and Balan study the impact on quality of care of a consummated merger between two hospitals in the Chicago suburbs (Evanston Northwestern Hospital and Highland Park Hospital).…”
mentioning
confidence: 99%